Perancangan Sistem Pendinginan Peltier Kapasitas 7 x 350 ml Darah - Tri Bambang Lesmana; Awaludin Martin (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2020)
Based on WHO Standards, Indonesia has not fulfilled the minimum blood supply for its 258 million populations. So, when needing certain types of blood that are available outside an area must go through the process of blood distribution. During this time, the distribution only uses ice packs in maintaining blood temperature. The use of ice packs in the distribution process is very risky because ice packs quickly adjust to the ambient temperature. Then, the temperature in the blood is feared more than the rule. Therefore, the design of blood carrier box with cooling components from the peltier element are intended to overcome the problem of blood distribution by being able to maintain blood in the temperature range of 2-10oC. The electrical power maximum of cooler design for 7x350 ml blood bags was obtained at 283.2 Watt. Keywords : Peltier Element, Blood Carrier Box